Mass Spectrometry-Based Method for Multiple Allergens Control: Application to Bakery Goods - Anna Luparelli; Elisabetta De Angelis; Rosa Pilolli; Francesca Lambertini; Michele Suman; Linda Monaci (Foods)
In recent years, mass spectrometry has played a key role as a confirmatory method to unequivocally identify multiple allergens, increasing the level of protection of allergic consumers. Despite advances made in methods of development, food processing still represents a critical issue in terms of the detection and accurate quantification of allergens due to chemical/structural modifications that can occur on the protein moiety or interferences of matrix compounds that might impair their final detection. Based on the multi-allergen MS/MS method devised within the ThrAll project, in this paper, we investigated the applicability of the developed method for the detection of traces of allergenic ingredients including egg, milk, soy, almond, hazelnut, peanuts, and sesame in two different kind of food matrices, namely cookies and rusks. The products were produced at laboratory scale in a food pilot plant that underwent different technological and thermal treatments. The challenge was to validate, in these extensively processed foods, the selected proteotypic peptide-markers capable of tracing the culprit ingredients in baked goods despite the processing the foods had undergone for their production. To accomplish this goal, the multi-target method developed on a low-resolution MS platform was transferred to a high-resolution MS system, and the pre-identified markers were also checked and validated on the new platform in order to be considered robust markers able to be indistinctly used on both types of platforms. Finally, the sensitivity of the method in terms of the Limit of Detection (LOD) and Limit of Quantification (LOQ) was calculated and the effect of the processing conditions on allergens detection in both baked goods was also investigated.